Jaarverslag 1973 : Provinciale Dienst voor Cultuur. (Brugge : Provincie West-Vlaanderen, 1975)
Algoet, Eric ; Bilquin, Jean ; Bonduel, Roger ; Clicque, Robert ; Cobbaert, Jan ; De Keyser, Raoul ; Degobert, Guy ; Gentils, Vic ; Keil, Helene ; Nelles, Roger ; Maeyer, Marcel ; Servranckx, Victor ; Swimberghe, Gilbert ; Theys, Yvan ; Van Hoeydonck, Paul ; etc.
Nederlands
boek